Horizontal Fiscal Imbalance in Nepal: Measurement and Policy Implications - Bhattarai, Kumar (AMC Journal (Dhangadhi), 2025)
This study measured horizontal fiscal imbalance across Nepal’s provinces and local levels and assessed the role of fiscal transfers in addressing this imbalance. For this, the study employed static techniques, utilizing secondary data spanning the period from 2018/19-2022/23. Horizontal fiscal imbalance was measured using per capita GDP and per capita own revenue. The findings reveal that both provinces and local levels in Nepal display relatively unequal fiscal capacities. While HFI is moderate across provinces, it is significantly high across the local levels. Revenue sharing has positively contributed in addressing HFI at both the provincial and local levels. However, grants have had mixed effects: they slightly increased fiscal disparities across provinces while slightly reduced across local levels. Less developed provinces, like Karnali and Sudurpaschim saw improvements in fiscal capacity due to grants, despite an overall rise in fiscal disparities. At the local level, grants significantly boosted the per capita resources of rural municipalities, which tend to be more resource-deficient. Although fiscal transfers have played a positive role in addressing HFI, they remain insufficient. Therefore, there is a need to improve the current transfer system. This could involve expanding the range of taxes included under revenue sharing, adjusting the weights assigned to various factors in the formula used to determine revenue sharing and grants (particularly assigning greater weight to infrastructure development status) and incorporating relevant indicators, such as the per capita OR of provinces and local levels.